2017
DOI: 10.1002/jrs.5123
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectral variation for human fingernails of postmenopausal women is dependent on fracture risk and osteoporosis status

Abstract: Patients diagnosed with osteoporosis have reported loss of fingernail resilience as the disease progresses. Keratin is the predominant protein in human nail tissue, and its structure has been postulated to be different in fingernails clipped from subjects who have sustained fragility fractures and those who have not, which may offer a window into the donor's bone health. This study was designed to qualify these differences, which may lead to the development of a novel screening tool for fracture risk. Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The use of nail tissue, rather than bone, could possibly provide a simpler means of assessing fracture risk. Previous studies by the authors have hypothesised a relationship between human nail structure, osteoporosis, and fracture risk [9][10][11][12][13][14] due to common exposure to systemic factors for bone and nail. These studies have used Raman spectroscopy, an optical analytical technique for obtaining semi-quantitative and qualitative information on complex samples.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nail tissue, rather than bone, could possibly provide a simpler means of assessing fracture risk. Previous studies by the authors have hypothesised a relationship between human nail structure, osteoporosis, and fracture risk [9][10][11][12][13][14] due to common exposure to systemic factors for bone and nail. These studies have used Raman spectroscopy, an optical analytical technique for obtaining semi-quantitative and qualitative information on complex samples.…”
Section: Introductionmentioning
confidence: 99%
“…Beattie et al reported that Raman spectral variations of human fingernails of postmenopausal women is dependent on fracture risk and osteoporosis status. They find that general fracture risk is associated with a change in the structure and composition of keratin protein, whereas osteoporosis is associated with different protein structural changes and an increase in free acid groups . Buchwald, Okulus, and Szybowicz reported new insights into Raman spectroscopy as a tool of early dental caries detection.…”
Section: Biosciencesmentioning
confidence: 93%
“…The discrepant results may be due to the lack of a proper spectra baseline correction model. Positive relationships have been demonstrated by Beattie et al [ 36 ], who developed a baseline correction model using a singular value decomposition (SVD)-based method.…”
Section: Association Between Nail Protein and Bmdmentioning
confidence: 99%
“…Using a baseline spectra correction model, Beattie and associates evaluated the amino acid profile of nail keratin samples from both fracture and non-fracture samples [ 36 ]. The keratin from the fracture group had no evidence of S–S bonds and had a low content of basic and hydroxyl amino acids compared to the control samples.…”
Section: Association Between Nail Protein and Bmdmentioning
confidence: 99%
See 1 more Smart Citation